Distribution of births within a day in Anatolian Merino Sheep - KARABACAK, A; ZULKADIR, U (The Indian Journal of Animal Sciences, 2014)
This research was conducted to investigate the relevance of lamb sex, birth type and birth rate on birth distribution within the 24 h daily cycle in Anatolian Merino sheep. The aim is to find solutions to problems that could arise in this subject. Birth records from 981 ewes and their 1,175 lambs from 2010–2011 were used for the study. The twin birth rate was 19.78% and the females were 54.54% and males 45.46%. The percentage of lambs born between 22: 01 and 04: 00, 04: 01 and 10:00, 10: 01 and 16: 00, and 16: 01 and 22: 00 was 25.99%, 29.36%, 25.57% and 20.08% respectively. For sheep giving birth for the first time, the highest birth rate (27.18%) was between 04: 01 and 10: 00, while for sheep giving birth for the second, third or fourth time the percentages were 28.88, 31.78 and 29.26%, respectively, and the births occurred at the same time. In the study, 53.93% of births took place during daylight hours while 46.07% of births took place at night. The percentage of births between 22: 00 and 04: 00 was 25.99%.